Outpatient Negative-Pressure Wound Therapy Following Surgical Debridement: Results and Complications. (August 2018) - Tamir, Eran; Finestone, Aharon S.; Wiser, Itay; Anekstein, Yoram; Agar, Gabriel
ABSTRACT: OBJECTIVE: To present results and complications in a case series of outpatients with diabetic and neuropathic foot ulcers with exposed bone following surgical debridement treated with negative-pressure wound therapy (NPWT). METHODS: Retrospective data were obtained from digital medical records from the Maccabi Health Services High Risk Foot Clinic in Tel Aviv, Israel, between 2009 and 2014. Medical records examined were those of clinic outpatients with exposed bone following partial foot amputation or selective bone debridement (University of Texas grade III-A) treated with NPWT. MAIN OUTCOME MEASURES: Wound area, closure rate, and adverse events. MAIN RESULTS: There were 66 patients provided NPWT in a total of 77 treatment courses. Mean patient age was 62 ± 10 years, 82% were male, and mean diabetes mellitus duration was 14 ± 8 years. Mean HbA1C levels were 8.1% ± 1.7%. Mean treatment course duration was 16 days (range, 2–42 days). Wound area decreased significantly (from 11.3 ± 16.8 cm 2 to 8.0 ± 13.3 cm 2, P < .0001). Ulcer curing was noted in 7% of the cases, and healing progression was noted in 54%. Seven serious adverse events were recorded. CONCLUSIONS: Outpatient NPWT is a relatively safe and effective adjuvant to surgical debridement of neuropathic foot ulcers. In an outpatient setting, one can expect serious adverse events to occur in 10% of cases, but this seems unavoidable in patients with diabetic foot ulcers when taking into account their comorbidities and patient resources. Strict protocols to promote early recognition of complications and appropriate response to minimize deterioration must be implemented.